Enhancing midwives’ scope of practice: An innovative educational program for delivery suite operating rooms - Brown, Janie; Dunning, C.; Cavanagh, D.; Cross, L. (Slack Incorporated, 2015)
Background: This retrospective study examined the enhancement of practice, knowledge, and skill of delivery suite midwives undertaking the circulating and instrument roles during emergent caesarean sections following a tailored educational program implemented to the benchmark standard. Method: All midwives who attended the educational program were invited to participate (N = 48); a total of 20 responses were received. Descriptive data analysis of the bivariate nominal data was performed. Results: Clinically significant outcomes were noted across all theme areas: knowledge of the Australian College of Operating Room Nurses standards, competence and knowledge of the main roles during a caesarean section, knowledge of policies and procedures, and patient safety. An improved working relationship between the perioperative and delivery ward staff also was identified. Conclusion: An educational program for midwives on the instrument and circulating roles for caesarean sections provides the knowledge and skill development required for clinically safe practice.